Social Darwinist ideology, racism and conflict in selected hollywood films about Africa - Mkahlela, Olindah (Midlands State University, 2017)
The study focused on the Social Darwinist ideology, racism and conflict in selected Hollywood films about Africa looking at the case study of Tears of the Sun, Hotel Rwanda and Blood Diamond. The aim of the study was to interrogate the interaction of Social Darwinist ideology, race and conflict in selected Hollywood films about Africa with sub-objectives of establishing perceptions, determining conflict interpretations, assessing racial perspectives, identifying filmic techniques used and evaluating the effects of the techniques by Hollywood films.